Validação de radioimunoensaio para quantificação de leptina plasmática bovina - Beltran, Maria Paula [UNESP]; Nogueira, Guilherme de Paula (My University, 2010)
Due necessity of better understanding leptin and reproduction relations, a specific radioimmunoassay (RIA) to bovine leptin was avalidated. First, an antibody production protocol was developed using recombinant equine leptin inoculated in a rabbit, that results in 28,05% of maximum binding (MB) 105 days after the protocol beginning. The tests of validations verified parallelism between standard curve and dilutions of high and low controls (P < 0,01). Antibody against equine leptin showed specificity to bovine leptin (P < 0,01). The recuperation tax of bovine leptin by antibody against recombinant equine leptin was from 98,4 to 101,6% (P < 0, 01). When the samples were stored in ambient temperature or refrigerated to 4°C, ligation stability was verified (P > 0,2), however, temperatures above 37°C impaired the bovine leptin recuperation. The use of assay buffer with or without bovine plasma did not show any difference (P > 0,3). These results showed that the antibody produced in rabbit against equine leptin were able to detect plasmatic bovine leptin, and that the RIA to bovine leptin quantification had adequate characteristics to the development of a valid assay.
Imunoradioassay validation to plasmatic bovine leptin quantification
Keywords: Antibody; Leptin; Radioimmunoassay; Validation; Bovinae; Equidae; Oryctolagus cuniculus